Development of Special Relativity Material Learning Videos on Social Media Tiktok - Sholina, Wini; Muliyati, Dewi; Purwahida, Rahmah (MJI Publisher by PT Mitra Jurnal Indonesia, 2023)
The intensity of social media use by students is currently very high. TikTok social media is one of the social media that is often used because the videos that are presented are short and up to date. The purpose of this research is to develop physics learning videos on the TikTok platform with an introduction to physics concepts and cases in everyday life. This study uses the 4D method (Define, Design, Develop, Disseminate). The stages of the 4D method applied to this study are by analyzing needs and planning the concepts and content of video content. The product developed is in the form of a learning video on special relativity material and distributed via the social media TikTok. Media and material assessment instruments to measure validity by media experts and material experts. From the results of this study, show that learning videos on social media Tiktok is feasible to be implemented as a medium for learning physics in class 12 high school on special relativity material.